PENGARUH SPIRITUALITAS KERJA DAN DUKUNGAN ORGANISASI MELALUI KEPERCAYAAN TERHADAP KEPUASAN KERJA SUMBER DAYA MANUSIA - Fatma Cahya Kurniati (Jurnal Riset Bisnis Indonesia, 2015)
The purpose of this study to examine the influence of workplace spirituality, organizational support,trust to job satisfaction of human resources, case studies on the civil servants Government of Demak.Data collection by spread questionnaire on respondents, representatives of civil servants workingin 17 departments and agencies as Demak. The sample of this study as many as 80 people byusing proportional sampling. This study used a descriptive analysis to determine the characteristicsof respondents and descriptive of respondents for each indicator variable. The instrument used toexamine the relationship between variables using SEM methods and analysis techniques PLS (PartialLeast Square).The findings of this study indicate a significant positive relationship between workplacespirituality and job satisfaction. Workplace spirituality haven’t positive and impact relationship ontrust. Organizational support have significant positive effect on trust. Oganization support haven’tpositive and significant impact on job satisfaction and trust have positive and significant relationshipon job satisfaction. The implication is managers have to pay attention to the importance of workplacespirituality in civil servants the Government of Demak. By increasing understanding of workplacespirituality the job satisfaction will be obtained and professional state apparatur that would be realized.In addition, organizational support and trust should also be provided with a well that increased jobsatisfaction.Keywords: workplace spirituality, organizational support, trust, job satisfaction.